Unexpected record of Meadia roseni Mok, Lee & Chan, 1991 (Anguilliformes: Synaphobranchidae) from the Western Indian Ocean, with comments on its ontogenetic changes - Matiku, Patroba; Bogorodsky, Sergey V.; Samucidine, Kelvin; Matcher, Gwyneth; Bills, Roger; Tighe, Kenneth A. (Zootaxa, 2026)
Two specimens of a rare eel of the genus Meadia (Synaphobranchidae, Ilyophinae) were trawled during a survey conducted by the research vessel Dr. Fridtjof Nansen off Tanzania in 2023. Detailed examination and comparison with the three known species of the genus revealed that both specimens belong to Meadia roseni Mok, Lee & Chan, 1991, a species previously thought to be restricted to Taiwan and Vietnam. These specimens represent the first record of this species from the Indian Ocean. Species identification is supported by a phylogenetic analysis of the COI barcoding region, which included a specimen of M. roseni from Taiwan. Description of both Tanzanian specimens, based on voucher material, is provided and accompanied by photographs of fresh specimens. Ontogenetic changes associated with growth are also discussed.